2x.(x-5)-x.(2x+3)=26 (3y^2-y+1).(y-1)+y^2.(4-3y)=5/2 2x^2+3.(x-1).(x+1)=5x.(x+1) iu mụa nguoiwww 05/07/2021 Bởi Adalyn 2x.(x-5)-x.(2x+3)=26 (3y^2-y+1).(y-1)+y^2.(4-3y)=5/2 2x^2+3.(x-1).(x+1)=5x.(x+1) iu mụa nguoiwww
Đáp án: Giải thích các bước giải: 2x(x-5)-x(2x+3)=26 ⇔ x(2x-10-2x-3)=26 ⇔ -13x = 26 ⇔ x=-2 Vậy tập nghiệm pt S={-2} (3y²-y+1)(y+1)+y²(4-3y)=$\frac{5}{2}$ ⇔3y³-y²+y+3y²-y+1+4y²-3y³=$\frac{5}{2}$ ⇔ 6y²+1=$\frac{5}{2}$ ⇔ 6y²=$\frac{3}{2}$ ⇔ y²=$\frac{1}{4}$ ⇔ y= ±$\frac{1}{2}$ Vậy tập nghiệm pt S={±$\frac{1}{2}$} 2x²+3(x-1)(x+1)=5x(x+1) ⇔ 2x²+3x²-3=5x²+5x ⇔ 5x=-3 ⇔ x=$\frac{-3}{5}$ Vậy tập nghiệm pt S={$\frac{-3}{5}$} -Học tốt- Bình luận
Đáp án + Giải thích các bước giải: `2x.(x-5)-x.(2x+3)=26` `=>2x^2-10x-2x^2-3x=26` `=>-13x=26` `=>x=-2` Vậy `S={-2}` `—` `(3y^2-y+1).(y-1)+y^2.(4-3y)=5/2` `=>3y^3-3y^2-y^2+2y-1-3y^3+4y^2=5/2` `=>2y-1=5/2` `=>y=7/4` Vậy `S={7/4}` `—` `2x^2+3.(x-1).(x+1)=5x.(x+1)` `=>2x^2+3x^2-3-5x^2-5x=0` `=>-5x-3=0` `=>x=-3/5` Bình luận
Đáp án:
Giải thích các bước giải:
2x(x-5)-x(2x+3)=26
⇔ x(2x-10-2x-3)=26
⇔ -13x = 26
⇔ x=-2
Vậy tập nghiệm pt S={-2}
(3y²-y+1)(y+1)+y²(4-3y)=$\frac{5}{2}$
⇔3y³-y²+y+3y²-y+1+4y²-3y³=$\frac{5}{2}$
⇔ 6y²+1=$\frac{5}{2}$
⇔ 6y²=$\frac{3}{2}$
⇔ y²=$\frac{1}{4}$
⇔ y= ±$\frac{1}{2}$
Vậy tập nghiệm pt S={±$\frac{1}{2}$}
2x²+3(x-1)(x+1)=5x(x+1)
⇔ 2x²+3x²-3=5x²+5x
⇔ 5x=-3
⇔ x=$\frac{-3}{5}$
Vậy tập nghiệm pt S={$\frac{-3}{5}$}
-Học tốt-
Đáp án + Giải thích các bước giải:
`2x.(x-5)-x.(2x+3)=26`
`=>2x^2-10x-2x^2-3x=26`
`=>-13x=26`
`=>x=-2`
Vậy `S={-2}`
`—`
`(3y^2-y+1).(y-1)+y^2.(4-3y)=5/2`
`=>3y^3-3y^2-y^2+2y-1-3y^3+4y^2=5/2`
`=>2y-1=5/2`
`=>y=7/4`
Vậy `S={7/4}`
`—`
`2x^2+3.(x-1).(x+1)=5x.(x+1)`
`=>2x^2+3x^2-3-5x^2-5x=0`
`=>-5x-3=0`
`=>x=-3/5`